Underground Water Quality of Vagdod Taluka, North Gujarat, India - Joshi, J.D.; Vora, J.J.; Sharma, Sangita; Patel, N.K.; Kothari, O.K.; Salvi, K.N. (Asian Journal of Chemistry, 2016)
Chemical analysis of water samples of 25 borewells from different sites of Vagdod Taluka located in North Gujarat was carried out and the outcome of the results is discussed.